State’s Repression toward INGO: The Dismissal of Médecins Sans Frontieres from Ethiopia - Saadah, Kholifatus; Dyarsa, Aqbil Faza (WIMAYA, 2022)
The primary purpose of humanitarian-based INGOs is to provide and distribute assistance to those who could not get it. One of the INGOs engaged in this field and is quite successful in the international constellation is Medecins Sans Frontieres, often called Doctors without Borders. Humanitarian INGOs generally have a noble mission and have no mission to engage in the host country's political dynamics. However, the noble mission became a boomerang when MSF became one of the INGOs who worked to save the famine in Ethiopia. MSF has a noble mission, but the Ethiopian government has another mission that aggravates the condition of hunger in Ethiopia. As INGOs sought to be neutral, MSF decided to remain silent and take no steps relating to the political constellation of one of the world's poorest countries. Things got worse when MSF realized that one of their programs was being misused by the government to blackmail the guerrilla groups in the north. MSF could no longer remain silent and objected to any Ethiopian government policy related to them, resulting in the dismissal of all MSF members from Ethiopia at the end of 1986. This paper will explain the weak position of NGOs toward state, the main reason of the dismissal. The authors will be using the qualitative method by explaining the history about MSF and NGOs in the perspective of state which resulted the justification of the weak position of NGOs itself.